Examining Credit Financing and Profitability of Small-Scale Enterprises in Kabale Municipality: A Case Study of Selected Enterprises in Southern Division. - Mubangizi, Ronald (Kabale University, 2023)
The purpose of this study was to examine credit financing and profitability of small-scale enterprises in Kabale Municipality a case study of selected Enterprises in Southern Division.